Guided wave propagation in structural health monitoring (numerical analysis) - Lim, Chee Heng. (2010)
Bridges, buildings, roads and infrastructures are common sights in this modern society. Many countries had spent a fortune on building them and especially in maintaining this infrastructure. The main objective of this research is to study the feasibility of adopting smart material transducers to determine the health of a structure by reading an array of sensors that are embedded (permanently attached on structure) and monitored over time using lamb wave propagation. It replaces schedule maintenance with as-needed maintenance, on one hand, saving the cost of unnecessary maintenance, and on the other hand, preventing unscheduled maintenance. For this research, in order for elastic wave propagation to be readily understood, frequency of 100 kHz 5 count smooth tone burst excitation was chosen to be the actuation pulse. In the beginning, for simple analysis, 1-D modeling using nodal translations and rotations was used in simulating two forms of lamb waves, namely Axial waves S0 and flexural waves A0. Axial wave, S0, was chosen to be the better choice for crack-detection with the pulse echo method over flexural wave, A0. Further test was conducted to study the response of structure under actuation of PZT. Results shown that in order to obtain an ideal signal for crack detection, the utmost important factor would then be to determine the numbers and the locations of the actuating PZTs, including the sensors to be used and placed. With successful simulation while harnessing the varying operating and the environmental conditions of the structure, a more comprehensive and all rounded result could be obtained. Ultimately, the lifespan of a structure could be determined.